ANALISIS PENGARUH STRUKTUR MODAL, LIKUIDITAS, PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI PERIODE 2021–2023 - Doni Andreas (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the effect of capital structure, liquidity, and profitability on firm value in property sector companies listed on the Indonesia Stock Exchange during 2021–2023. Firm value is measured by Price to Book Value (PBV), while the independent variables include Debt to Equity Ratio (DER), Current Ratio (CR), Return on Assets (ROA), and Return on Equity (ROE). This research employs a quantitative approach with multiple linear regression analysis. The results indicate that DER and ROE have a significant negative effect on PBV, while CR and ROA show no significant effect. The implication of this research is that companies need to maintain a prudent capital structure and improve earnings quality to increase investor confidence.